Ordinance No. 1492, §§ 1-5, Olympia City Council (1917) (Olympia, Washington). - (:unkn) unknown (My University, 1917)
It shall be unlawful for any person, firm or corporation, to purchase any gun, pistol, firearm or other deadly weapon, or any ammunition or explosive of any kind or character, without first obtaining a written permit therefor from the Chief of Police of the City of Olympia.
Keywords: LICENSE - DEALERS